Design of an Efficient Water Pump System to Support Ablution Water Needs at Al-Amalul Khair Islamic Boarding School - Baiti Hidayati; Fenoria Putri; Muhammad Rizky Tolusha Putra; Nadiyah Rohmatullah; Azis Mukhtamar; Pravin Cheti A/L Jayakumar (Alesha Media Digital, 2026)
The community service program, in collaboration with Madrasah Tsanawiyah Al-Amalul Khair in Palembang, aims to address the urgent need for an efficient water pump system, replacing the existing labor-intensive, unhygienic manual pulley system. The school, with approximately 388 students and 27 staff, faces difficulties meeting daily water demand of 1,500–3,000 liters, resulting in long queues and hygiene issues that disrupt religious and learning activities. The program's objectives include designing an energy-efficient pump with a capacity of at least 0.8 liters/second, providing a 1,500–3,000 liter storage tank and automatic sensors, and offering training on pump operation, maintenance, and troubleshooting. Additionally, sustainability will be ensured through manuals, internal technical teams, and partnerships. The method involves outreach, training workshops, installation, mentoring, and performance evaluation. Expected outcomes are a reliable, hygienic, energy-efficient water pump system, improved ablution facilities, operational manuals, a trained technical team, and enhanced capacity to manage water facilities, reducing costs. Ultimately, the program will improve religious practices, health standards, and overall comfort in the learning environment.